Soil heavy metal contamination in rural land consolidation areas in the Yangtze River Delta, China - Zeng, Jingjing; Zhou, Shenglu; Lv, Ligang; Su, Quanlong; Wang, Jing (Journal of Environmental Engineering and Landscape Management, 2018)
Due to the rapid urbanization of the Yangtze River Delta in China, large numbers of formerly rural residents have migrated to the cities. To adjust the structure of rural land use, the government has performed extensive land consolidation. Previous studies indicated that the land consolidation has affected farmland quality to some extent. However, the effect of the land consolidation on farmland heavy metal concentrations has rarely been reported. In this study, the Jintan District was used as an example, and 40 sampling sites of various consolidation types in 4 representative areas of rural land consolidation were selected. Soil samples were collected from these sites, and the heavy metal concentrations were analyzed. We used multivariate methods of correlation analysis and principal component analysis to study the conditions and sources of the heavy metal contamination in the soil. The results indicate that the mean concentrations of Cd, Hg, Ni, Cu, and Zn in the soil all exceeded the background values. The mean concentration of Cd was 0.409 mg/kg, and the enrichment factor (EF) was 4.54, making Cd the most prevalent heavy metal soil contaminant in the study area. The enrichment of soil heavy metals varied among the various representative areas. Suburban areas surrounding the central cities were mainly enriched in Hg, with an EF of 6.20. The comprehensive development zone displayed enrichment in Cd, with an EF of 7.79. The heavy metal concentrations in the soil also differed depending on the type of land consolidation. The reclaimed soil of rural settlements contained high levels of Cd and Zn, with EFs of 7.25 and 2.52, respectively, which were related to the land use before the land consolidation. The soil heavy metals of the study area were affected by both human activity and natural background contamination.